2014
DOI: 10.3791/52122
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Electron Microscopy of the <em>Helicobacter pylori</em> Cag Type IV Secretion System Pili Produced in Varying Conditions of Iron Availability

Abstract: Helicobacter pylori is a helical-shaped, gram negative bacterium that colonizes the human gastric niche of half of the human population 1,2 . H. pylori is the primary cause of gastric cancer, the second leading cause of cancer-related deaths worldwide 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Role of ATPase activity on the above processes, however, could not be established. Not much is known about pilus biogenesis in Hp except a few recent reports [ 8 , 39 , 45 , 46 ]. In Hp prototypical pilus subunits are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Role of ATPase activity on the above processes, however, could not be established. Not much is known about pilus biogenesis in Hp except a few recent reports [ 8 , 39 , 45 , 46 ]. In Hp prototypical pilus subunits are missing.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the Fur regulated genes that are transcriptionally upregulated upon iron starvation facilitate the acquisition and trafficking of iron within the bacterial cell [ 60 62 ]. For example, when iron availability is low H. pylori increases the transcription of the high-affinity iron transporters feA1, fecA2, frpB1 , and feoB facilitating an influx of iron into the cytoplasm [ 60 65 ]. Additionally, H. pylori increases binding of the host chelating proteins, lactoferrin and transferrin, upon iron starvation, both of which can be used as a source of nutrient iron.…”
Section: H Pylori and Nutritionmentioning
confidence: 99%
“…Similarly, the human antimicrobial protein lactoferrin, which serves as an iron source for H. pylori , has been shown to repress the expression of both cagA and vacA , indicating that the human antimicrobial response can directly alter H. pylori virulence by altering the micronutrient gradient available to this bacterial pathogen [ 59 , 68 ]. Recently, our work has indicated that the biogenesis and activity of the cag- T4SS increase upon iron starvation [ 65 , 66 ]. Together these findings indicate that regulation of H. pylori toxin secretion is mediated by iron availability and that both toxins play a critical role in iron homeostasis.…”
Section: H Pylori and Nutritionmentioning
confidence: 99%
“…Given its role in immune modulation and iron acquisition, it is not surprising that Fur has been implicated as a potential regulator of cagA expression (Pich et al, 2012 ; Vannini et al, 2014 ). Along with these observations, our work has shown that conditions of low nutrient iron availability induce expression of the Cag-T4SS pili at the host-pathogen interface, and also enhance the activity of the Cag-T4SS (Noto et al, 2013 , 2014 ; Haley et al, 2014 ). Additionally, transcription of cagA has shown to be upregulated in iron-replete conditions suggesting Fe-Fur activation of cagA (Pich et al, 2012 ).…”
Section: Ironmentioning
confidence: 57%